Dinamika Pergelaran Jaran Kepang di Kota Malang dalam Perspektif Antropologi - Hanifati Alifa Radhia (Universitas Gadjah Mada, 2017)
The hobby-horse dance as known as jaran kepang, jathilan or kuda lumping is the one of dance art performance from Javanese. It also know as well in Malang City. Jaran kepang is one of entertainment art which have magic dramatical as the climax in the end of performance. It happend when one of the jaran kepang dancer was trance. This jaran kepang performance was invited and entertain folks to see and, it potentially to be carnaval event. Before they perform, called gebyak, the jaran kepang dancer do some rites to called their danyang or perewangan, and prepare sesaji or sandingan. The dynamic of art performance both personal or collective grup reflected the reality of traditional art performance in Indonesia. Today, this jaran kepang performance who had ritual function was changed by entertainment. Jaran kepang as culture is one of Javanese rural rites in selamatan or bersih desa moment. This paper was done by through context perspective with life history analysis. The aim of research is to see the social-cultural phenomena behind jaran kepang performance.